An Error Analysis In Arranging Structure Of Noun Phrase Made By The Eleventh-Grade Students Of SMA N 2 Muaro Jambi - Riski Safitri; Desi Eka Putri; Efendi Efendi; Veni Veni; Septiana Vratiwi; Yanti Nazmai Ekaputri; M. Iqbal Liayong Pratama (Departement of Mathematics Education, 2023)
The research study aimed to determine the errors that eleventh-grade students of SMA N 2 Muaro Jambi made in arranging the structure of noun phrases and the dominant errors that students made in arranging the structure of noun phrases. The method used in this research is descriptive. The population is the eleventh-grade students of SMA N 2 Muaro Jambi. The sample taken through the cluster random sampling technique was class XI IPA 1. This research used a test as the instrument to collect the data. The test showed that the students made more errors in arranging the structure of noun phrases were additions. The percentage of errors was 45,18%.On the contrary, the lowest errors that the students made in arranging the structure of noun phrases were misorderings, and the percentage was only 10,37%. From the result of this research, it can be concluded that the students were confused about arranging the structure of noun phrases especially related to addiction. It was caused by the lack of knowledge about common noun functioning as modifiers to modify the Noun in noun phrases.